2021
DOI: 10.3389/fonc.2021.735817
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chemotherapy in Survival of Stage I Nasopharyngeal Carcinoma

Abstract: PurposeTo identify whether chemoradiotherapy improves survival of stage I nasopharyngeal carcinoma (NPC).Materials and MethodsNPC patients were extracted from the Surveillance, Epidemiology, and End Results database between 2010 and 2015. Pathologically confirmed stage T1N0M0 (the 7th edition AJCC) were investigated. Overall survival (OS) and cancer-specific survival (CSS) were compared between the radiotherapy and chemoradiotherapy groups using the Kaplan-Meier method and propensity score matching (PSM) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nasopharyngeal carcinoma is a common malignant tumor occurring in the head and neck, and its pathological type is mostly squamous cell carcinoma [ 14 ]. The patients with nasopharyngeal carcinoma do not have specific symptoms in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma is a common malignant tumor occurring in the head and neck, and its pathological type is mostly squamous cell carcinoma [ 14 ]. The patients with nasopharyngeal carcinoma do not have specific symptoms in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials and observational studies used the median age at diagnosis as the cutoff value to divide patients into 2 groups. [12][13][14][15][16] Several studies reported that age at diagnosis was not an independent prognostic factor. Nevertheless, some suggested that median age is an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%